SISTEM PAKAR DIAGNOSIS PENYAKIT KUCING BERBASIS ANDROID - simanjorang, Sandar arihman; Karnadi, Very (Computer Science and Industrial Engineering, 2020)
Batam has a variety of pets, one of them is a cat is indeed one type of pet that is popular tobe maintained especially in the city of Batam. Cats are very adorable animals, withbeautiful body shapes and feathers. This is why many people choose cats as a fun pet. Butcats are also prone to disease attacks. Increasing the interest of the wider community inmaintaining cats makes more and more information about how to maintain and maintaincats well, without needing to bring to veterinary clinics or veterinary physicians. However,the majority of cat owners are lacking in understanding the health of his pets. So the cat ismore susceptible to disease and does not close the possibility of transmit to humans. Lackof knowledge on the maintenance of cat health and disease management is feared canmake cat disease increasingly severe. In fact, proper care in cats determines the health ofthe cat. The expert system is very helpful and relieves work in finding out about the catdisease suffered without having to go where the expert. To facilitate decision making, theForward chaining method is required.